Midbrain organoids with an SNCA gene triplication model key features of synucleinopathy. Issue 4 (25th September 2021) - Mohamed, Nguyen-Vi; Sirois, Julien; Ramamurthy, Janani; Mathur, Meghna; Lépine, Paula; Deneault, Eric; Maussion, Gilles; Nicouleau, Michael; Chen, Carol X -Q; Abdian, Narges; Soubannier, Vincent; Cai, Eddie; et al.
Abstract: SNCA, the first gene associated with Parkinson's disease, encodes the α-synuclein protein, the predominant component within pathological inclusions termed Lewy bodies. The presence of Lewy bodies is one of the classical hallmarks found in the brain of patients with Parkinson's disease, and Lewy bodies have also been observed in patients with other synucleinopathies. However, the study of α-synuclein pathology in cells has relied largely on two-dimensional culture models, which typically lack the cellular diversity and complex spatial environment found in the brain. Here, to address this gap, we use three-dimensional midbrain organoids, differentiated from human-induced pluripotent stem cells derived from patients carrying a triplication of the SNCA gene and from CRISPR/Cas9 corrected isogenic control iPSCs. These human midbrain organoids recapitulate key features of α-synuclein pathology observed in the brains of patients with synucleinopathies. In particular, we find that SNCA triplication human midbrain organoids express elevated levels of α-synuclein and exhibit an age-dependent increase in α-synuclein aggregation, manifested by the presence of both oligomeric and phosphorylated forms of α-synuclein. These phosphorylated α-synuclein aggregates were found in both neurons and glial cells and their time-dependent accumulation correlated with a selective reduction in dopaminergic neuron numbers. Thus, human midbrain organoids from patients carrying SNCA gene multiplication can reliably model key pathological features of Parkinson's disease and provide a powerful system to study the pathogenesis of synucleinopathies. Abstract : Mohamed et al. investigate synucleinopathy in human midbrain organoids, derived from patients carrying a triplication of the SNCA gene. Human midbrain organoids recapitulate pathology observed in the brains of patients: an elevated level of α-synuclein, an age-dependent increase in aggregation and a selective reduction in dopaminergic neurons. Graphical Abstract: